The Novel Coronavirus and Enforcement of the New Separate System in Prisons - Klein, Michael (Criminal justice policy review, 2022)
Coronavirus has had a significant impact on daily life. Prisons are not exempt from the impact of coronavirus disease 2019 (COVID-19). Prisons are particularly at risk due to their secure environment and vulnerable inmate populations. We examine steps taken by the 50 state departments of correction and the Federal Bureau of Prisons to mitigate COVID-19 as reported on their websites. While states vary in their response to the virus, those responses do not appear to be related to regional or political differences. Few are testing or quarantining all inmates, and there are more proactive responses devoted to staff than inmates in their facilities. Findings demonstrate that prison systems’ policies regarding COVID-19 testing, quarantining, and provision of personal protective equipment for inmates do not fully align with Centers for Disease Control and Prevention recommendations. As a result, the steps prison systems are taking to mitigate the effect of COVID-19 may be more reactionary than proactive, which may be less effective overall.